2007
DOI: 10.1089/thy.2007.0001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histopathological, and Molecular Characteristics of Papillary Thyroid Microcarcinoma

Abstract: Many patients with PTMC had clinical and histopathological poor prognostic factors. The expression of molecular markers, such as EGFR and COX-2, may have a role in the prognosis of PTMC. When considering all of the prognostic factors, a more tailored management approach appears to be necessary for patients with PTMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 40 publications
(59 reference statements)
1
59
1
3
Order By: Relevance
“…In agreement with this, EGFR and VEGFR2 overexpression has been shown to be closely correlated to advanced tumor stage, metastasis, and poor clinical outcome in several human cancers. With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this, EGFR and VEGFR2 overexpression has been shown to be closely correlated to advanced tumor stage, metastasis, and poor clinical outcome in several human cancers. With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to thyroid carcinomas, EGFR overexpression has been detected in most anaplastic tumors (Schiff et al 2004, Wiseman et al 2007, Elliott et al 2008 and to a much lower extent in PTCs (Schiff et al 2004, Murakawa et al 2005, Mitsiades et al 2006, Lim et al 2007, Elliott et al 2008. In PTC, EGFR expression has been associated to poor prognosis (Akslen & Varhaug 1995, Chen et al 1999, although not always (Lim et al 2007), and recent studies have suggested that EGFR inhibitors might be active against anaplastic thyroid carcinomas (Lopez et al 2008). In thyroid neoplasias, overexpression of VEGF and platelet-derived growth factor receptor have been described, and disruption of VEGF signaling has been shown to inhibit thyroid cancer cell growth in vitro and in vivo (Tuttle et al 2002, Turner et al 2003, Lin & Chao 2005, Vieira et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that the absence of epidermal growth factor receptor expression was positively correlated with the presence of lymph node metastases (23). Some studies evaluated whether the expression of cyclin D1 and galectin-3 in PTMC could be a marker of lymph node metastases (145)(146)(147).…”
Section: Risk Factors For the Presence Of Lymph Node Metastases At DImentioning
confidence: 99%
“…Assessing the MIB-1 in evaluating proliferative activity and predicting the aggressiveness of the tumor types is very useful (Nakayama et al, 2007;Pesutic-Pisac et al, 2008;Pujani et al, 2010;Ranjbari and Rahim, 2013). In spite of the fact the index of the Ki-67 cell marker (ki-67 labeling index = LI) for the diagnosis of thyroid neoplasms has been studied but the relationship between the papillary thyroid carcinoma and the ki-67 LI and the biological behavior is not well understood (Lim et al, 2007;Pujani et al, 2010). Some studies conducted on patients with the PTMC with the high ki-67 LI levels, obviously demonstrated that they had the lower disease-free survival and higher rates of the disease recurrence, compared with the PTMC and PTC (macro carcinoma) with Low Ki-67 LI (Hay et al, 1992;Siironen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%